Kontroversi Akad Nikah Secara Daring - Herdiansa (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. The terms and conditions of marriage are things that must be considered in the marriage contract. One of the pillars of shigat in marriage is ittihād al-majlis (being in the same assembly). Nowadays, marriage contract activities can be carried out from different places due to developments in technology, information and communication. The marriage contract carried out online (because of different locations) appears to be contrary to the pillars and requirements of ittihād al-majlis. Aim. The function and aim of research on the practice of online marriage contracts in general is to increase knowledge in the scientific discourse of Islamic law and provide legal understanding regarding the phenomenon of online marriage contracts for readers. Methods. The data analysis used in the research is qualitative research with a normative approach using the library research method (library study), which is research by reviewing literature related to the object of research regarding online marriage contract controversies, both primary and secondary references. This research is descriptive-analytic in nature, in the process it will describe and analyze matters relating to the object of research regarding the online marriage contract controversy. Results. Online marriage contracts receive legal certainty by issuing a fatwa from the fatwa institution regarding the validity of online marriage contracts. Decisions regarding the legality of carrying out online marriage contracts can be found in existing jurisprudence. And Mafhum mukholafah communicating long distance online has become a habit which then makes parties who are far away become closer and belong to the same assembly and according to the author this has fulfilled the elements contained in ittihād al-majlis.